Experimental Investigation of a Novel Solar Micro-Channel Loop-Heat-Pipe Photovoltaic/Thermal (MC-LHP-PV/T) System for Heat and Power Generation. (15th December 2019) - Yu, Min; Chen, Fucheng; Zheng, Siming; Zhou, Jinzhi; Zhao, Xudong; Wang, Zhangyuan; Li, Guiqiang; Li, Jing; Fan, Yi; Ji, Jie; Diallo, Theirno M.O.; Hardy, David
Highlights: A novel MC-LHP-PV/T heat and power system was experimentally investigated. New PV/T system achieved 18.55% higher solar efficiency compared to existing ones. A lower inlet water temperature led to the increased solar thermal efficiency. A higher water flow rate help increase the solar thermal efficiency. A higher ambient temperature led to the increased solar thermal efficiency. Abstract: This paper aims to experimentally investigate a novel solar Micro-Channel Loop-Heat-Pipe Photovoltaic/Thermal (MC-LHP-PV/T) system which, making its first attempt to employ the co-axial tubular heat exchanger as the condenser, PV-bound multiple micro-channel tubes array as the PV/evaporator, the upper end liquid header with tiny holes as the liquid header and liquid/vapour separator, and the upper end vapour header as the vapour collector and distributor, can create the improved condensation and evaporation effects within the loop-heat-pipe (LHP) and thus, achieve significantly enhanced solar thermal and electrical efficiencies compared to traditional PV/T systems. Based on the results derived from our previous analytical study, a prototype MC-LHP-PV/T system employing R-134a as the working fluid was designed, constructed and tested, and the testing results were used to evaluate its operational performance including solar thermal and electrical efficiencies and their relevant impact factors. It is found that solar thermal efficiency of the MC-LHP-PV/T system varied with the inlet temperature and flow rate of coolant water, ambient temperature, as well as height difference between the condenser and evaporator. A lower inlet water temperature, a higher water flow rate, a higher ambient temperature, and a larger height difference between the condenser and the evaporator can help increase the solar thermal efficiency of the system. Under a range of testing conditions with the refrigerant charge ratio of 30%, a peak solar thermal efficiency (i.e., 71.67%) happened at solar radiation of 561W/m 2, inlet water temperature of 18°C, water flow rate of 0.17m3/h, ambient temperature of 30°C, and height difference of 1.3m. This set of parametrical data is therefore regarded as the optimal operational condition of the MC-LHP-PV/T system. Under these specific operational condition and the real weather solar radiation, the solar thermal efficiency of the system was in the range 25.2% to 62.2%, while the solar electrical efficiency varied from 15.59% to 18.34%. Compared to the existing PV/T and BIPV/T systems, the new MC-LHP-PV/T system achieved 17.20% and 33.31% higher overall solar efficiency.